Home page for accesible maths 2 Chapter 2 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

2.4 Partial differentiation from first principles

Example.

To find the partial derivatives of f(x,y)=x2+xyf(x,y)=x^{2}+xy.

Solution.

Let (x,y)=(a,b)(x,y)=(a,b). To determine fx\frac{\partial f}{\partial x} we need to calculate the change that occurs in the value of ff for a small change hh in the value of xx. Thus we consider f(a+h,b)=(a+h)2+(a+h)b=a2+2ah+h2+ab+bh.f(a+h,b)=(a+h)^{2}+(a+h)b=\,{a^{2}+2ah+h^{2}+ab+bh.} Then

fx=limh0f(a,b+h)-f(a,b)h=limh0(2a+b+h)=2a+b.\frac{\partial f}{\partial x}=\lim_{h\rightarrow 0}\frac{f(a,b+h)-f(a,b)}{h}=% \,{\lim_{h\rightarrow 0}(2a+b+h)}\,{=2a+b.}

Similarly, f(a,b+k)-f(a,b)=a2+a(b+k)-a2-ab=ak.f(a,b+k)-f(a,b)=a^{2}+a(b+k)-a^{2}-ab=\,{ak.} Therefore

fy=limk0f(a,b+k)-f(a,b)k=a.\frac{\partial f}{\partial y}=\lim_{k\rightarrow 0}\frac{f(a,b+k)-f(a,b)}{k}={% a.}